Práticas de leitura em um hospital do município de Vitória, ES - Santana, Clediluce (2012)
This thesis aims to analyze the reading practices that are performed in the hospital with children and adolescents in health care. The work tries to understand what they read, what is the conception of reading, language, text, subject, and their practices. In addition, it also tries to understand what are the brackets and text genres commonly used by teachers in a hospital class. The research was based on the Bakhtinian conception of language as verbal interaction, and the methodology was characterized as a case study of a qualitative nature. The work consists in the use of participant observation and individual interviews with teachers, children and adolescents. The methods were worked out to characterize them, as well as with daily field records of observation, photography and film events. It was possible to find out that children and adolescents in the hospital read a variety of genres such as fairy tales, fables, chronics, informative newspapers, explanatory opinions, entries, poems, poetry, music, comics, trivia, myth, legend, adventure, rhyme, and others. The teachers allowed the reading of these genres in different ways: aloud individual reading, silent reading, and collective reading helped by the teacher for those beginning in literacy. To read the work, the teachers have also used various media such as paper, whiteboard, magazines, books and xerox copies of known literature. The survey examined the reading of stories, legends, and entries and found out that the conceptions of reading, language, and text justifying the practices of the teachers were not homogeneous. The reading was crafted, sometimes restricted to the mere deciphering of signs, ie, decoding and writing. On the other hand, the reading sometimes was allowed to vary broadly and the dialogue was very exploited, leading to a complex reading activity and production of meaning and senses.